Ultra endurance athletes at-risk - Edler, J. R.; Wassink, M. L.; Kahanov, L.; Eberman, L. E. (International Journal of Athletic Therapy & Training, 2014)
The article discusses the risk associated of cardiovascular events and sudden cardiac death of the athletes which participated in the ultra endurance events such as cycling and running. It mentions that the injuries and illnesses due to ultra endurance events including hyperthermia, bursitis and tendonitis and the need of the nutrients and the supplements in the diet of athletes for enhancing the performance. It concludes that ultra endurance events cause the increased strain on body.